The Role and Function of microRNA in the Pathogenesis of Multiple Myeloma - Handa, Hiroshi (Cancers (Basel), 2019)
Recently, attention has been drawn to the role of non-coding regions of the genome in cancer pathogenesis. MicroRNAs (miRNAs) are small non-coding RNAs with 19–25 bases of length that control gene expression by destroying messenger RNA or inhibiting its translation. In multiple myeloma (MM), the expression of several miRNAs, such as miR-15a and miR-16, is markedly decreased and their target genes upregulated, suggesting their role as tumor-suppressing miRNAs. In contrast, miRNAs such as miR-21 and miR-221 are highly expressed and function as oncogenes (oncomiRs). In addition, several miRNAs, such as those belonging to the miR-34 family, are transcriptional targets of p53 and mediate its tumor-suppressive functions. Many miRNAs are associated with drug resistance, and the modulation of their expression or activity might be explored to reverse it. Moreover, miRNA expression patterns in either MM cells or serum exosomes have been shown to be good prognostic markers. miRNA regulation mechanisms have not been fully elucidated. Many miRNAs are epigenetically controlled by DNA methylation and histone modification, and others regulate the expression of epigenetic modifiers, indicating that miRNA and other epigenetic effectors are part of a network. In this review, we outlined the roles of miRNAs in MM and their potential to predict MM prognosis and develop novel therapies.